Débriefer l’activité des élèves : une étude conversationnelle et didactique du débriefing de type corrigé des activités expérimentales lors de l’enseignement de la chimie en seconde - Rita Khanfour-Armalé; Jean François Le Maréchal (Recherches en Éducation)
This article focuses on the teacher debriefing of student activity in secondary chemistry classes. The main objective of this particular moment of teaching is that teachers structure the knowledge involved by the students during the labwork. The methodological approach used articulates the conversational analysis and the didactic analysis using the facets of knowledge. Conversational and didactic study of feedback debriefing reveals that the class discussion is structured as ternary exchanges (teacher question, student response, teacher evaluation) and limits the educational scope. This case study gives suggestions of changes to the feedback debriefing so that the teachers can take them into account in their preparations